2014
DOI: 10.1177/1403494814556926
|View full text |Cite
|
Sign up to set email alerts
|

Academic practice–policy partnerships for health promotion research: Experiences from three research programs

Abstract: The fundamentals of a genuine partnership are communication, collaboration, shared visions, and willingness of all stakeholders to learn from one another.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 51 publications
2
45
0
Order By: Relevance
“…This study addresses a gap in the literature related to limited information on the factors and processes that may explain the quality of partnerships; in fact, we lack suitable indicators to assess well‐functioning health promotion partnerships. Most studies relied on qualitative evaluations of specific case studies (e.g., Eriksson, Fredriksson, Froding, Geidne, & Pettersson, ; Estacio et al, ) and did not consider the role that developing a sense of community may play, giving more attention to other processes, like leadership management and negotiation procedures (Stolp et al, ). Only few studies (McNeish et al, ; Powell & Peterson, ) have recently addressed the role of sense of community in perceived effectiveness of community coalitions, providing evidence that sense of community is a key process in enhancing the perception of coalition effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…This study addresses a gap in the literature related to limited information on the factors and processes that may explain the quality of partnerships; in fact, we lack suitable indicators to assess well‐functioning health promotion partnerships. Most studies relied on qualitative evaluations of specific case studies (e.g., Eriksson, Fredriksson, Froding, Geidne, & Pettersson, ; Estacio et al, ) and did not consider the role that developing a sense of community may play, giving more attention to other processes, like leadership management and negotiation procedures (Stolp et al, ). Only few studies (McNeish et al, ; Powell & Peterson, ) have recently addressed the role of sense of community in perceived effectiveness of community coalitions, providing evidence that sense of community is a key process in enhancing the perception of coalition effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…This study is part of a larger study focusing on “School as a setting for alcohol and drug prevention” in a special venture financed by the Swedish government [50, 51]. The program was designed and implemented by the NGO, and the research team was responsible for the research and evaluation activities.…”
Section: Methodsmentioning
confidence: 99%
“…We identified several key factors that helped to build the CAP and to sustain the relationships between the partners over the past seven years [9,10]. Consistent with the findings of Eriksson et al, [17] mutual respect and a shared vision led to shared goals and built a strong foundation for the partnership. The HCNI team built upon this foundation by incorporating five key themes for building and sustaining the partnership: trust, transparency, equity and fairness, need for adequate resources and importance of developing protocols.…”
Section: Discussionmentioning
confidence: 53%
“…The idea of community and academia partnering in the research process leads to the need for a better understanding how to build and sustain such partnerships. There are several examples in the literature of "how to" build a Community-Academic Partnership (CAP) [9][10][11][12][13][14][15][16][17], but developing effective CAPs is challenging [18], and the steps to build and sustain these CAPs have not been well documented. Most reports of CAPs have instead focused on discussing accomplishments [19][20][21][22], while a few studies have reported on selected elements of successful collaborations, such as building trust and team-building activities [23,24].…”
Section: Introductionmentioning
confidence: 99%